2018
DOI: 10.1002/jls.21570
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self‐Attention in Leader Development

Abstract: The ability to identify emerging leaders and to facilitate their leader development, is paramount for maintaining sound leadership within organizations, across time. However, research into the proximal antecedents of leader development remains in its infancy. The current longitudinal study sought to broaden current perspectives on the role of self‐attention in promoting leader development, namely growth in leader self‐efficacy and self‐reported emergence into leader roles. The leader development of a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Purposefully engaged leaders are dedicated to and absorbed in activities and are invigorated by their pursuit. Some research indicates that leader development is helped by reflective self‐attention, a way of thinking about oneself that creates a positive spiral of self‐discovery (Steele & Day, ). There is a sense of positive energy and possibility as a leader work toward his or her ideal self.…”
Section: Purposeful Engagementmentioning
confidence: 99%
“…Purposefully engaged leaders are dedicated to and absorbed in activities and are invigorated by their pursuit. Some research indicates that leader development is helped by reflective self‐attention, a way of thinking about oneself that creates a positive spiral of self‐discovery (Steele & Day, ). There is a sense of positive energy and possibility as a leader work toward his or her ideal self.…”
Section: Purposeful Engagementmentioning
confidence: 99%
“…Cerni et al (2014b) argue that thinking adaptively will allow leaders to better select and apply effective, rather than ineffective, styles of leadership and leadership behaviours. Indeed, Steele and Day (2018) have demonstrated that reflective thinking, much like that described as rational thinking in CET, is related to leaders' ability to develop their leadership practices. Second, rational thinking should relate to specific ‘rational’ effective leader behaviours such as ‘intellectual stimulation’, which is a component of transformational leadership, ‘rational persuasion’, an effective influence tactic, and to general problem‐solving, which is needed in order to manage conflict.…”
Section: Figurementioning
confidence: 99%
“…Indeed, this possibility has been demonstrated by Cerni, Curtis, and Colmar's (2010) study, which found that coaching leaders to improve their thinking styles significantly increased their other‐rated transformational leadership scores. In addition, Steele and Day (2018) have recently found that how leaders think is an important antecedent to the effectiveness of development that they undertake in their roles. To date, thinking styles have only been measured via self‐reports in the organisational psychology literature, and so the present study suggests that an alternative method that overcomes social‐desirability bias concerns may have some utility.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Several studies have suggested that promoting reflective thinking about leadership, and leaders’ meta-cognition more generally, is related to improved leader performance and development ( Cerni et al, 2010a ; Steele and Day, 2018 ). Cerni (2015) , in particular, has argued for the use of CET in guiding leaders’ reflection through coaching to better understand how their thinking is related to their behaviors as a leader.…”
Section: Discussionmentioning
confidence: 99%
“…Second, rational thinking is associated with several other psychological variables that are related to good leadership per se and transformational leadership specifically. Rational thinking is positively associated with intelligence, adaptability, and conscious self-awareness, all of which are associated with transformational and/or effective leadership ( Epstein, 1998 ; Van Vugt, 2006 ; Yukl and Mahsud, 2010 ; Steele and Day, 2018 ).…”
Section: Cognitive-experiential Leadership Modelmentioning
confidence: 99%